Socialism and legal history : the histories and historians of law in socialist East Central Europe - Erkkilä, Ville 1978- HerausgeberIn; Haferkamp, Hans-Peter 1966- HerausgeberIn (Routledge research in legal history, 2021)
The transformations of some classical principles in socialist Hungarian civil law : the metamorphosis of 'bona fides' and 'boni mores' in the Hungarian Civil Code of 1959 / András Földi -- We few, we happy few? Legal history in the GDR / Martin Otto -- Roman law studies in the USSR : an abiding debate on slaves, economy and the process of history / Anton Rudokvas and Ville Erkkilä -- Strategies of covert resistance : teaching and studying legal history at the University of Tartu in the Soviet era / Marju Luts-Sootak -- The Western legal tradition and Soviet Russia : the genesis of H. J. Berman's Law and Revolution / Adolfo Giuliani -- Juliusz Bardach and the agenda of socialist history of law in Poland / Marta Bucholc -- Valdemārs Kalniņš (1907-1981) : the founder of Soviet legal history in Latvia / Sanita Osipova -- Getaway into the Middle Ages? : on topics, methods and results of 'socialist' legal historiography at the University of Jena / Adrian Schmidt-Recla and Zara Luisa Gries -- Roman law and socialism : life and work of a Hungarian scholar, Elemér Pólay / Éva Jakab.